A BRIEF RADIOGRAPHIC REPORT FROM TWO COMMON ODONTOGENIC CYSTS IN JAWS WITH FOLLICULAR RADIOLUCENT APPEARANCE - Adineh Javadian Langaroodi; Seyed Hossein Hoseini Zarch; Amin Rahpeyma; Nasim Khaki; Alireza Esmaeilzade; Hamed Ebrahimnejad (Cumhuriyet University, 2017)
Objectives: Pericoronal radiolucencies are common pathologic findings in regular dental checkups. Since dentigerous cyst is the most common pathologic pericoronal radiolucency and as odontogenic keratocyst (OKC) is a common cyst also and an aggressive lesion with high recurrence, radiographic features of these lesions were discussed in this study using panoramic radiography and cone beam computed tomography.Materials and Methods: In this cross-sectional case series study, radiographs from 56 patients who were referred to  a private maxillofacial radiology center or  dentistry faculty in Mashhad/Iran from 2008 to 2013 in which radiolucent pericoronal lesion was observed in jaws with histopathologic results of dentigerous cyst or OKC were separately examined by two maxillofacial radiologists. Both observers were unaware of pathology results. Lesions were assessed based on their location, periphery, and impaction on the surrounding structures. Then, obtained data were analyzed using descriptive tables. Results: 56 lesions were identified in 56 patients. There were 20 odontogenic keratocyst and 36 dentigerous cysts. The majority of dentigerous cysts and OKCs occurred in the posterior mandible and showed a well corticated border. External root resorption was higher in OKC cases. In addition, displacement tendency of surrounding structures (other than tooth) such as nasal floor, mandibular canal, buccal and lingual cortex (in the form of expansion) as well as destruction of cortex, nasal floor or sinus walls was higher in OKC than in dentigerous cyst. Conclusion: Except of tooth displacement other parameters related to the effect on surrounding structures in this study showed higher frequency in OKC than dentigerous cyst.